Solutions to promote exports of Ca Mau province in the period of 2021 – 2025 - Bùi, Minh Tiến (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Export is an important economic sector for localities in Vietnam, and especially important for Ca Mau province, where economic development conditions are limited. Export activities will contribute to foreign currency revenue, create jobs, attract foreign investors, contribute to the development of other industries and fields of the province, and at the same time effectively exploit the province’s potential and strengths. The study of the export situation in Ca Mau province, in the period 2017 - 2021, is based on collected data, summarizes the export situation, and analyzes the data collected from the primary and secondary data set. The research article was conducted with the following objectives: (1) Analyzing the export situation in Ca Mau province in the period of 2017 - 2021 to find out the strengths that need to be promoted and the shortcomings and causes that need to be improved; (2) Proposing solutions to promote export of Ca Mau province in the period of 2021 - 2025.